The Emergence of Civil Disobedience: a Comparison during Dr. Mahathir and Abdullah Badawi's Era - Mohd. Zain, Zawiyah (MCSER Publishing, Rome-Italy, 2015)
Civil disobedience is not new in Malaysia. It has been going on since the days of Tunku Abdul Rahman. However, it did not explode until the final phase of the reign of Dr. Mahathir in 1998. While in 2007 there was widespread civil disobedience when people were not satisfied with the administration of Abdullah Badawi.The purpose of this article is to analyze the factors that caused at the time of the occurrence of civil disobedience during the era of Dr. Mahathir and Abdullah Badawi. Results show that the main reason for the occurrence of civil disobedience at the time of Dr. Mahathir was due to the grievances of the people on the issue of the dismissal of Anwar Ibrahim. Whereas at the time of Abdullah Badawi the emergence of civil disobedience is caused by the weakness of his leadership. In addition, the analysis also found that civil disobedience affect the outcome of the general elections in 1999 and 2008 when the Barisan Nasional (National Front) performance deteriorated badly in the General Elections. The Barisan Nasional decline in the general election of 2008 resulted in Abdullah Badawi’s resignation in April 2009